16S rRNAgene‐based metagenomic analysis of the gut microbial community associated with the DUI species Unio crassus (Bivalvia: Unionidae). (2nd March 2020) - Mioduchowska, Monika; Zając, Katarzyna; Bartoszek, Krzysztof; Madanecki, Piotr; Kur, Jarosław; Zając, Tadeusz
Abstract: What factors determine biome richness: genetic or environmental? Sex, phylogeny, and tolerance indicated by other symbionts (e.g., endosymbionts) or simply is it related to local habitat, especially if the gut biome is considered? To answer these questions, we investigated the gut microbial profile of both sexes of three Unio crassus populations, species with unique system of mitochondrial DNA inheritance called doubly uniparental inheritance (DUI), living in different ecological conditions. High‐throughput sequencing of the V3–V4 hypervariable regions in the bacterial 16S rRNA gene fragment was performed, which resulted in a total of 1, 051, 647 reads, with 58, 424 reads/65 OTUs (operational taxonomic units) per sample on average. We identified a core microbiome, with all individual mussels sharing 69 OTUs (representing 23% of the total number of OTUs). Proteobacteria was the dominant phylum in all samples, followed by Firmicutes, Actinobacteria, and Bacteroidetes. There were no significant differences in gut microbiome compositions between the two sexes of this species; however, we observed different phyla in geographically isolated populations. A non‐metric multidimensional scaling plot and dendrogram showed that the bacterial profile complies with the genetic structure of populations. Although we found differences in microbiomes between populations, their genetic structure suggests that the microbiome is weakly related to habitat, and more strongly to phylogeography (on both F and M mitotypes). We found no significant differences in beta diversity between the individuals of the bacterial communities measured using the Bray–Curtis index. Finally, we also examined whether OTUs were represented by symbiotic bacteria that enable cellulose digestion and by endosymbiotic bacteria that play important functions in the biology of their hosts and also affect microevolutionary processes and population phenomena. With regard to the endosymbionts, however, there was no relation to sex of the studied individuals, which suggests that there are no straightforward relations between DUI and microbiome. Abstract : We examined the gut microbial profile of both sexes of three Unio crassus populations, species with unique system of mitochondrial DNA inheritance called doubly uniparental inheritance (DUI). We identified a core microbiome, with all individual mussels sharing 69 OTUs (representing 23% of the total number of OTUs). Proteobacteria was the dominant phylum in all samples. There were no significant differences in gut microbiome compositions between the two sexes of this species; however, we observed different phyla in geographically isolated populations.